SURVEI PEMAHAMAN SISWA TENTANG GAYA BELAJAR DI SMP NEGERI 8 PALANGKA RAYA - Sitorus, Sabar Halimah; Pangestie, Esty Pan; Apriatama, Dony (Universitas Nias Raya, 2023)
Learning style is a person's way of absorbing and obtaining information in learning, but many students still do not know the learning style that is in them. This study aims to determine students' understanding of learning styles and to find out the learning styles (Visual, Audio, Kinesthetic) of students at SMP Negeri 8 Palangka Raya. This type of research is quantitative research with a survey method with the Purposive Sampling technique. The population in this study were all students of class VIII with a total of 351 students with 88 students as a sample member. This research was conducted in October 2022. Data collection was carried out using a questionnaire which was distributed via the Google form. Based on the research results, it is known that students' understanding of learning styles is in the